2022
DOI: 10.3390/biomedicines10112972
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic Abuse, Dependence, and Withdrawal in the Pediatric Population: A Real-World Disproportionality Analysis

Abstract: Antipsychotic drugs (APs) aim to treat schizophrenia, bipolar mania, and behavioral symptoms. In child psychiatry, despite limited evidence regarding their efficacy and safety, APs are increasingly subject to off-label use. Studies investigating addictology-related symptoms in young people being scarce, we aimed to characterize the different patterns of AP misuse and withdrawal in children and adolescents relying on the WHO pharmacovigilance database (VigiBase®, Uppsala Monitoring Centre, Sweden). Using the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…The network also includes known drugs of abuse ( e.g. , opioids, ethanol, promethazine) and widely prescribed drugs with potential for misuse, including antipsychotics ( e.g., aripriprazole 33,34 ( OPRM1 ), dosulepin 35 ( ADRA1D ), olanzapine 33 ( GABRG3 ), pipamperone 33 ( ADRA1D ), quetiapine 33,36 ( ADRA1D ) and benzodiazepines ( e.g. , alprazolam 37 , lorazepam 38 , temazepam 38 that all target GABRE and GABRG3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The network also includes known drugs of abuse ( e.g. , opioids, ethanol, promethazine) and widely prescribed drugs with potential for misuse, including antipsychotics ( e.g., aripriprazole 33,34 ( OPRM1 ), dosulepin 35 ( ADRA1D ), olanzapine 33 ( GABRG3 ), pipamperone 33 ( ADRA1D ), quetiapine 33,36 ( ADRA1D ) and benzodiazepines ( e.g. , alprazolam 37 , lorazepam 38 , temazepam 38 that all target GABRE and GABRG3 ).…”
Section: Resultsmentioning
confidence: 99%
“…This includes the drug spironolactone (targeting CACNB2 and PGR), which has recently been investigated for treating AUD 30 , and multiple approved antidepressants 31,32 such as amitriptyline (ADRA1D, NTRK2, OPRM1), amoxapine (ADRA1D, GABRE, GABRG3), and esketamine (BDNF, NTRK2). The network also includes known drugs of abuse (e.g., opioids, ethanol, promethazine) and widely prescribed drugs with potential for misuse, including antipsychotics (e.g., aripriprazole 33,34 (OPRM1), dosulepin 35 (ADRA1D), olanzapine 33 (GABRG3), pipamperone 33 (ADRA1D), quetiapine 33,36 (ADRA1D) and benzodiazepines (e.g., alprazolam 37 , lorazepam 38 , temazepam 38 that all target GABRE and GABRG3). A number of opioids are also present in the drug-gene target network based on their characterized effects on OPRM1.…”
Section: Conceptual Model Of Biological Pathways Underlying Opioid Ad...mentioning
confidence: 99%
“…Meanwhile, these guidelines have indicated that early use of antipsychotics (APs) could reduce or delay the onset of psychosis. According to the underlying mechanism, Aps are categorized into typical and atypical antipsychotics, also known as first-generation antipsychotics (FGAs) and second-generation antipsychotics (SGAs), for the treatment of schizophrenia, bipolar disorders and other behavioral disorders [8,9]. Compared to FGAs, SGAs have fewer neurological adverse reactions but are associated with a greater risk of metabolic adverse events [10,11].…”
Section: Introductionmentioning
confidence: 99%